Evaluation of Wound Healing Property of Terminalia catappa on Excision Wound Models in Wistar Rats - Khan, A. A.; Kumar, V.; Singh, B. K.; Singh, R. (Drug Research, 2014)
Wound is defined as the loss of breaking cellular and functional continuity of the living tissues. Management of wounds is frequently encountered with different problems. Drug resistance and toxicity hindered the development of synthetic antimicrobial agents with wound healing activity. Many plants with potent pharmacological activities may offer better treatment options viz. Terminalia chebula, Terminalia bellirica and Phyllanthus emblica formulations have shown healing activities on wounds.The present study was planned to investigate the wound healing activity of Terminalia catappa on excision wound model in rats. Ointment was prepared by using bark extract of Terminalia catappa in soft paraffin and preservative. Wistar albino rats (200–250 gm) of either sex were used in the present study. A circular wound of 2 cm in diameter was made on the depilated dorsal thoracic region of the rats under ether anesthesia in aseptic conditions. The ointment was applied for 18 days and percent wound closure observed along with the parameters viz. Epithelization, granuloma weight and scar formation. Animals were observed on 3rd, 6th, 9th, 12th, 15th and 18th post-wounding day.Wound healing activity was compared with that of control and Betadine ointment as standard drug. Animals treated with Terminalia catappa ointment exhibited 97% reduction in wound area as compared to the control animals (81%). Ointment treated wounds were found to induce epithelization faster compared to the control. In conclusion, Terminalia catappa ointment promotes significant wound healing in rats and further evaluation of this activity in humans is suggested.
Keywords: wound healing; Terminalia catappa; excision wound model; epithelization; wound contraction